SLO dan FPIC dalam Tata Kelola Pertambangan Nikel: Studi Socio-Legal atas Konflik Lahan dan Kriminalisasi Masyarakat di Kabupaten Kolaka, Indonesia - Umirul Ham (CV WAHANA PUBLIKASI, 2026)
The expansion of nickel mining in Indonesia has become a strategic foundation for the mineral downstreaming agenda and the global energy transition. However, at the local level, such expansion often generates serious social conflicts, particularly concerning land control and the criminalization of communities. This study critically analyzes how the concepts of Social License to Operate (SLO) and Free, Prior and Informed Consent (FPIC) operate or fail to materialize in the governance of nickel mining in Kolaka Regency, Southeast Sulawesi. Using a qualitative socio legal approach based on literature review and case studies, this research finds that mining legitimacy in Indonesia remains dominated by a legal license paradigm that prioritizes investment certainty and state and corporate power, while sidelining the social legitimacy of local communities. The main findings reveal a systematic pattern of dispossession of community land access through state licensing instruments, accompanied by the criminalization of residents who resist or question mining operations. In this context, SLO is reduced to a post facto conflict management instrument through CSR and PPM programs, while FPIC is neither normatively institutionalized nor practically implemented. This study argues that the failure to realize SLO and FPIC in Kolaka is not merely an issue of implementation, but rather a consequence of the legal and political structures of extractivism that position the state and corporations in asymmetrical power relations with local communities. The contribution of this study lies in strengthening socio legal analysis on legitimacy, power, and justice in the governance of nickel mining in Indonesia, with Kolaka presented as a primary case.